2020
DOI: 10.3389/fpls.2020.01235
|View full text |Cite
|
Sign up to set email alerts
|

Stressed to Death: The Role of Transcription Factors in Plant Programmed Cell Death Induced by Abiotic and Biotic Stimuli

Abstract: Programmed cell death (PCD) is a genetically controlled pathway that plants can use to selectively eliminate redundant or damaged cells. In addition to its fundamental role in plant development, PCD can often be activated as an essential defense response when dealing with biotic and abiotic stresses. For example, localized, tightly controlled PCD can promote plant survival by restricting pathogen growth, driving the development of morphological traits for stress tolerance such as aerenchyma, or triggering syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 161 publications
(183 reference statements)
0
40
0
Order By: Relevance
“…Whether the HR mechanism leads to systemic cell death (TN), delayed TN, or restricted vein necrosis (VN) is controlled by other proteins that recognize specific pathogen effectors, such as receptor molecules like RLK and NBS-LRR proteins. Moreover, several families of transcription factors have been discovered to regulate programmed cell death and HR, including members of bZIP, MBY, NAC, ERF, and WRKY ( Burke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the HR mechanism leads to systemic cell death (TN), delayed TN, or restricted vein necrosis (VN) is controlled by other proteins that recognize specific pathogen effectors, such as receptor molecules like RLK and NBS-LRR proteins. Moreover, several families of transcription factors have been discovered to regulate programmed cell death and HR, including members of bZIP, MBY, NAC, ERF, and WRKY ( Burke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PCD is a controlled process and is a consequence of high ROS and NO levels typically up-regulated by ABA ( Petrov et al, 2015 ; You and Chan, 2015 ). In plants, PCD is often an adaptive response during abiotic/biotic stress ( Fagundes et al, 2015 ; Burke et al, 2020 ). However, PCD can also aggravate plant disease ( Huysmans et al, 2017 ).…”
Section: Subsequent Effects Of Aba Besides Stomatal Closure Towards Amentioning
confidence: 99%
“…The NAC family is one of the largest plant-specific TF families with 110 genes in Arabidopsis [ 36 ] and 150 genes in rice [ 37 ]. NAC TFs are involved in responses to biotic and abiotic stresses and are key regulators of cross-talk between signaling pathways implicated in adaptation to environmental challenges [ 38 , 39 , 40 , 41 ]. In accordance with this, whole-genome expression studies in Arabidopsis showed that most NAC genes are induced by at least one type of abiotic stress signal [ 36 ].…”
Section: Id In Plant Tfsmentioning
confidence: 99%